Effect of tissue inhibitor of metalloproteinases 3 on DLK1 shedding in cultured human pre-adipocytes and implications for adipose tissue remodelling. (26th February 2015) - Fenech, Matthew; Gavrilovic, Jelena; Turner, Jeremy
Abstract: Background: Metabolically unhealthy obesity is associated with adipose tissue inflammation and increased risk of type 2 diabetes. Dysfunctional adipose tissue remodelling has been implicated in development of metabolically unhealthy obesity, but the pathogenesis remains poorly characterised. We hypothesised that in health, tissue inhibitor of metalloproteinases 3 (TIMP3) modulates adipose tissue remodelling by regulating extracellular matrix turnover and shedding of the adipogenic regulator DLK1, but that in adipose tissue inflammation it might drive development of metabolically unhealthy obesity. Methods: Primary pre-adipocyte and in-vitro-differentiated adipocyte cultures were established from abdominal subcutaneous adipose tissue donated by healthy women undergoing breast reconstruction. Cells were seeded onto collagen I, and subsequently treated with differentiation medium or tumour necrosis factor (TNF) alpha (50 ng/mL). Adenoviral transduction allowed TIMP3 overexpression. Media and lysates were collected for quantitative RT-PCR, and immunoblot and hydroxyproline release assays. Statistical analysis was performed with t testing or ANOVA. Findings: Induction of differentiation in human pre-adipocytes reduced TIMP3 mRNA levels by 75% (n=3, p<0·0001). Hydroxyproline release by differentiating pre-adipocytes was 2·3 times greater than that by control-treated cells (mean 5·66 μg/mL [SD 0·77] vs 2·45 [0·36], p<0·0001) indicating greater collagen I degradation. TNF alpha reduced TIMP3 mRNA levels by 66% in in-vitro-differentiated adipocytes (n=3, p<0·0001); reduced TIMP3 expression was confirmed by western blot. Shedding of soluble DLK1 (sDLK1) by pre-adipocytes was increased by TNF alpha and by overexpression of adenovirally delivered TIMP3 compared with control conditions, as confirmed by immunoblot (n=3). Addition of recombinant human sDLK1 (500 pM) to pre-adipocyte cultures reduced adipogenesis, as assessed by oil red O staining (n=2). Interpretation: We have shown that TIMP3 is downregulated in adipogenesis, and by inflammatory signals in adipocytes. Furthermore, TIMP3 modulates sDLK1 shedding and collagen I degradation. TIMP3 is known to inhibit ADAM17 (DLK1 sheddase) and MMP14 (implicated in extracellular matrix turnover). TIMP3 might therefore integrate inflammatory signals with adipose remodelling. Subversion of remodelling pathways by chronic adipose inflammation might lead to maladaptive adipose expansion and metabolically unhealthy obesity. Funding: British Heart Foundation, Diabetes Research and Wellness Foundation Open Funding 2011.